2010
DOI: 10.1080/0972060x.2010.10643839
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oil ofThymus migricusKlokov & Desj.-Shost. from Iran

Abstract: Thymus migricus Klokov & Desj.-Shost. was collected at full flowering stage fromNorthwest of Iran. The essential oil of the air-dried aerial parts was obtained by hydrodistillation with a yield of 1.8 % (w/w). The essential oil was analyzed by combination of GC and GC-MS. Twenty compounds were identified, representing about 99.2 % of the total detected constituents. The main constituents of the essential oil were thymol (55.6 %), γ-terpinene (16.7 %), geraniol (4.6 %), pcymene (4.0 %), limonene (2.6 %) E-Caryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…While, α ‐humulene and β ‐caryophyllene were the major sesquiterpene hydrocarbons, β ‐cedrene epoxide and α ‐bisabolol were identified as the main oxygenated sesquiterpenes ( Table ). Literature survey on studies related to the EOs obtained from the plants belonging to Lamiaceae family, showed high variability in their chemical composition depending on genetic, location, and stages of plant development …”
Section: Resultsmentioning
confidence: 99%
“…While, α ‐humulene and β ‐caryophyllene were the major sesquiterpene hydrocarbons, β ‐cedrene epoxide and α ‐bisabolol were identified as the main oxygenated sesquiterpenes ( Table ). Literature survey on studies related to the EOs obtained from the plants belonging to Lamiaceae family, showed high variability in their chemical composition depending on genetic, location, and stages of plant development …”
Section: Resultsmentioning
confidence: 99%
“…Essential oils have a high heat capacity and can prevent damage to the plant in heat stress conditions by storing heat [ 41 ]. Negative correlations between altitude and essential oil content have been reported in previous studies conducted on M. longifolia [ 16 , 18 , 19 ], Thymus migricus [ 42 ], Thymus kotschyanus [ 43 ], and Achillea millefolium L. subsp. millefolium [ 44 ].…”
Section: Resultsmentioning
confidence: 73%
“…Thymus fallax (TF) and Thymus migricus (TM) (Lamiaceae) are naturally grown in east side of Turkey. According to previous studies, the essential oils (EOs) contents were determined in different regions as Turkey, Iran, and Azerbaijan and they were evaluated for some biological activities as antioxidant, antimicrobial, and antispasmodic 1 , 2 , 3 , 4 , 5 . Aim of our study is determining composition and total phenolic contents of EOs obtained from aerial parts of the plants by hydrodistillation and evaluating in vitro antidiabetic and antioxidant activities of EOs.…”
mentioning
confidence: 99%